STRATEGI KOMUNIKASI TOKOH HINDU KECAMATAN GERUNG GUNA MEMOTIVASI PEMUDA UNTUK KULIAH DI IAHN GDE PUDJA MATARAM - I Komang Widya Purnama Yasa (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2022)
Hindu figures have an important role in motivating Hindu youth. In this case, Hindu leaders need a strategy in basic communication to be able to answer what problems can be overcome the issues they have. This communication strategy is structured because of the various information obtained in advance so that there is a more effective and efficient discussion related to Hindu youth education. This study aims to find out what communication strategies are used by Hindu leaders in Gerung District to foster the motivation of Hindu youth in their environment to open their minds so they can choose to study at IAHN Gde Pudja Mataram. The approach used in this research is qualitative. Theories used in revealing the forms and processes that occur are interpersonal communication theory, phenomenological theory, and Communication Strategy. The location of this research is in Gerung Utara District, West Lombok Regency. Data collection techniques in this study through observation, interviews and documentation. The purposive technique determined informants. The results of this study indicate that there are two stages, namely planning and management, to achieve a goal. At the planning stage, the process of analyzing in advance the problems in the environment, knowing the wishes of Hindu youth, determining the goals to be achieved by Hindu figures, determining topics to be discussed and raised by Hindu leaders, and determining the delivery media. While at the management stage it has a process of exposure and education to Hindu youth and supervision and evaluation of Hindu youth.